PENGEMBANGAN SEKOLAH BERTARAF INTERNASIONAL MELALUI ORGANISASI BELAJAR: KONSEP DAN IMPLEMENTASI - Slamet Suyanto (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractIndonesian Government, putting into action the Educational System Law, isstarting its efforts this year to develop schools to reach international standardschools (SBI). The Educational System Law (2003), specifically act number 20, statesthat The government and/or district develop at least one school in every level tobe promoted into an international standard school (SBI). That act arises manyquestions in the school level concerning the international standards school (SBI),such as what is SBI, what is the main goal, what is the requirement of schools to bepromoted as SBI, how can schools develop themselves to reach SBI, what is thecriterion of the success? Indeed, there are many ways for schools to developthemselves into an international level. Every school may use a different way thatsuitable to the schools condition. This paper brings to mind the LearningOrganization (LO) as one of the generic promising ways to develop a school into aninternational level. LO is basically an organization that learns and doescontinuously improvement. LO comprises of five major components: (1) sharedvision, (2) system thinking, (3) personal mastery, (4) mental models, and (5) teamlearning. Besides, there are five subsystems where those components should bedeveloped in LO: (1) learning, (2) knowledge, (3) technology, (4) people, dan (5)organization.Keywords: SBI, organisasi belajar, learning organization